Assessing effects of legacy nuclear waste on plants: Sensitive fern (Onoclea sensibilis) gametophyte viability at the Chalk River site. (May 2020) - Stuart, Marilyne; Brinkmann, Lars; Festarini, Amy; Hehn, Melanie; Bowman, Meghan; Litalien, Amélie; Lapointe, Marie-Claude; Rowan, David
Abstract: We evaluated the effects of chronic exposure to environmental radiological contamination on the reproductive fitness of sensitive fern (O noclea sensibilis ) by quantifying viability in haploid gametophytes of spores collected from ferns from background and contaminated areas of the Chalk River site. Dose rates measured in situ at field sites ranged from 60 to 849 μGy h −1, with effects possible at the more contaminated sites (greater than 400 μGy h −1 ). Fern spores were also irradiated from 1 to 1000 Gy to develop dose-response curves. We found no effects on gametophyte viability at the most contaminated areas of the Chalk River site, where we estimated growing season doses of 0.3–3.7 Gy. Dose-response curves show evidence of hormesis, with an increase in gametophyte viability up to 10 Gy, followed by a rapid decline to no viable gametophytes at doses of 1000 Gy. The sensitive fern is not a radiosensitive plant species, but effects do occur within the normal range (10–1000 Gy) of most plant species, making it useful as a sentinel species from a community perspective. Sensitive fern spore germination is high and stable over field dose ranges, with effects primarily on gametophyte viability. This method shows promise as an effects monitoring tool for sites with radiological contamination. Highlights: Effects of environmental radiological contamination on the reproductive fitness of sensitive fern were evaluated. Dose rates measured in situ at field sites ranged from 60 to 849 μGy h −1 . No effects on gametophyte viability were noted at the most contaminated areas of the Chalk River site.